Specific features and mechanisms of fatigue in the ultrahigh-cycle regime - Mughrabi, Hael (International Journal of Fatigue, 2006)
Earlier concepts of ultrahigh-cycle fatigue (UHCF) of both ductile single-phase type I materials that do not contain inclusions and type II materials, e.g., high-strength steels containing non-metallic inclusions as (internal) crack initiation sites, are extended. In particular, the multi-stage fatigue life diagrams with a conventional high-cycle fatigue (HCF) limit and a possible lower fatigue limit in the UHCF range are discussed for both classes of materials in terms of the relevant fatigue cracking mechanisms. In this context, it is emphasized that it is important to consider in both cases details of fatigue crack initiation as a life-determining factor in the HCF and, even more so, in the UHCF regime. Different factors such as the density, size, location and distribution of non-metallic inclusions and details of specimen geometry and surface quality in the case of type II materials are discussed with respect to their influence on the transition stress separating the ranges of surface and internal fatigue cracking and with regard to fatigue lives. © 2006 Elsevier Ltd. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Ductile single-phase materials; Fatigue crack initiation; Fatigue life diagrams; Fatigue limit; High-strength steels; Inclusions; Surface versus subsurface failure